Essentials of Applied Mathematics for the Managerial Life and Social Sciences: Custom Publishing - Tamby Che, Siti Paridah
Essentials of Applied Mathematics for the Managerial, Life, and Social Sciences is customized to meet three main objectives, (1) to provide a text that is motivating while providing the background in the quantitative technique necessary to better understand and appreciate the course normally taken in undergraduate training, (2) to lay the foundation for more advanced courses, such as statistics and operations research, and (3) to make the text a useful tool for instructors.